2015
DOI: 10.1371/journal.pone.0127306
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Combining Antiangiogenic Agents with Chemotherapy for Patients with Advanced Non-Small Cell Lung Cancer Who Failed First-Line Chemotherapy: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe clinical outcomes of patients with NSCLC who progressed after first-line treatments remain poor. The purpose of this study was to assess the advantage of antiangiogenic therapy plus standard treatment versus standard treatment alone for this population of patients.MethodsWe conducted a rigorous search using electronic databases for eligible studies reporting antiangiogenic therapy combined with standard second-line chemotherapy versus standard second-line treatment for patient who progressed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(36 reference statements)
0
14
1
1
Order By: Relevance
“…Therefore, anti-angiogenesis has represented a new approach for targeted cancer therapy [6]. Recent clinical studies have demonstrated patients with advanced SCLCs benefitting further from anti-angiogenic therapy, when combined with chemotherapeutic regimes [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, anti-angiogenesis has represented a new approach for targeted cancer therapy [6]. Recent clinical studies have demonstrated patients with advanced SCLCs benefitting further from anti-angiogenic therapy, when combined with chemotherapeutic regimes [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, numerous studies suggested angiogenesis inhibitors were generally demonstrated to be effective to NSCLC. [4144] Particularly, Gao et al [45] conducted a meta-analysis encompassing over 452 advanced NSCLC patients who previously received bevacizumab and found that angiogenesis inhibitors improved clinical benefits. Therefore, different subtypes of diseases should be considered when using angiogenesis inhibitors in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis acts as one of the essential alterations occurring in cells during malignant transformation (56), since the delivery of oxygen and nutrients, provided by blood vessels, is required for cell survival and proliferation. Different molecules, inhibiting the angiogenic regulators, have been tested in combination with second-line chemotherapy (pemetrexed and docetaxel) in patients with NSCLC, but with disappointing results (62). Only recently, two drugs, interfering with the angiogenic pathways, nintedaninb and ramucirumab, have received the regulatory approval in association with docetaxel in the second-line setting.…”
Section: Comments and Future Perspectivesmentioning
confidence: 99%